Is climate exacerbating the root causes of conflict in Mali? A climate security analysis through a structural equation modeling approach - Pacillo, Grazia; Kangogo, Daniel; Madurga-Lopez, Ignacio; Villa, Victor; Belli, Anna; Läderach, Peter (Frontiers in Climate, 2022)
Climate change continues to pose significant challenges to human existence. Notably, in the past decade, the focus on the role of climate change on conflict and social unrest has gained traction in academic, development, and policy communities. This article examines the link between climate extremes and variability and the probability of conflict and violence. It advances the argument that climate is a threat multiplier, in their words, climate indirectly affects conflict occurrence. The mechanism at play is that climate creates resource scarcity which exhibits itself through increased household food insecurity. The increased food insecurity on the other hand exacerbates the root causes of conflict. We use the Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA), a nationally representative data from Mali which we merge with location-specific climate data. We employ a three-step econometrics approach to answer our research questions. The results support our hypothesis that climate is a threat multiplier. Specifically, we find evidence that temperature anomalies negatively affect agricultural production (total harvest), which adversely affects household food insecurity (household skipping meals and reducing the quantities of food consumed). This, in turn, increases the probability of conflict and violent events. Our findings suggest that efforts to build peace and security and climate resilience should account for the role of climate in exacerbating the root causes of conflict.